Safety in numbers? The effect of network competition on cybersecurity - Carolyn Gideon; Christiaan Hogendorn (International Telecommunications Society (ITS), 2014)
Economic incentives for security investment in elements of the Internet is of increasing concern. This paper contains an exploration of the incentives for Internet service providers (ISP)s to invest in security. The analysis focuses on the spillover effects of ISP security investments to other ISPs, which may be serving a different market or competing in the same market. The findings show that the nature of these spillover effects can change the effect competition in the ISP market has on incentives for investment in cybersecurity by the ISPs.
Keywords: 330